Effectiveness of a Bystander Intervention Program to Increase Bystander Behaviors Across Latent Risk Groups of High Schoolers - Mennicke, Annelise (Journal of interpersonal violence, 2024)
Bystander intervention programs have established efficacy to increase bystander behaviors to prevent interpersonal violence (IPV). Little research has investigated intervention efficacy among latent risk classes among high school students. Data from a five-year randomized control trial were used to conduct multigroup path analyses to assess the association between type of training received and bystander outcomes moderated by risk groups identified via latent profile analysis (LPA). LPA was used to identify risk based on six indicators related to violence exposure, association with aggressive friends, and alcohol use. Bystander training received was the primary independent variable characterized as: no training, overview speech alone, or skills training. Outcomes included (a) observed bystander behaviors; (b) reactive bystander behaviors; or (c) proactive bystander behaviors. Three risk groups were identified via LPA: low risk, moderate risk witnesses of IPV, and highest risk victims and perpetrators. Of the bystander trainings received, overview speeches only increased reactive bystander behaviors among low risk students. The skills training was effective at increasing most bystander outcomes among all risk groups, with the largest effect sizes observed among the highest risk victims and perpetrators profile. Findings suggest that tailoring or modifying bystander training based on the risk profiles of youth may lead to greater potential to increase bystander behaviors to reduce risk of violence. Specifically, overview speech trainings should be targeted to low risk youth, while skills training primarily delivered to higher risk youth. These skills trainings could incorporate content related to trauma-informed care as well as associations with alcohol use, which may enhance their effectiveness further.